Direct anastomosis indwelling needle puncture: a rapid and safe transitional hemodialysis access for patients with renal failure - Chunyan Wu; Jianbo Qing; Xiaoping Wang; Yunmei Li; Xin Zhou; Junnan Wu (Renal Failure)
Objectives Vascular access thrombosis (VAT) is a common complication in patients with end-stage renal disease (ESRD), significantly impacting hemodialysis efficacy and patient survival. Currently, temporary dialysis access is typically established via deep vein catheterization (VC), however, this method is highly invasive and associated with risks of infection and other complications. This study aims to explore the feasibility of using direct anastomosis indwelling needle puncture (DAINP) for temporary dialysis access.Methods Between March 2023 and March 2024, patients VAT were recruited at Sir Run Run Shaw Hospital of Zhejiang University School of Medicine to undergo DAINP. Clinical data, including age, gender, dry and wet body weight, and blood biochemical parameters, were collected. Patient VA types, locations, and insertion vessels were documented. Detailed assessments and records of VAT were performed for all patients, including the distance of thrombus from the anastomosis, residual blood flow at the VA anastomosis, and corresponding selection of the DAINP insertion site. Ultrasound was utilized to measure and record the puncture depth. Concurrently, clinical data of patients undergoing venous catheterization (VC) for temporary dialysis access were collected. The operative time for both groups, defined as the interval from ultrasound assessment initiation to completion of the procedure, was recorded and compared.Results A total of 74 patients successfully underwent DAINP, with a 100% puncture success rate. Among them, 20 patients had residual blood flow at the VA stump, and the distance between the anastomosis and arterial flow was ≥ 1 cm. Patients with VA located at the elbow demonstrated the greatest puncture depth. Moreover, the operative time for the DAINP group was significantly shorter compared to the 17 patients who underwent VC for VAT during the same period. However, patients with VA located in the groin required a longer operative time for DAINP.Conclusions This study demonstrates that DAINP provides a rapid and safe method for establishing temporary hemodialysis access in VAT patients, effectively reducing the invasiveness and risks associated with traditional VC.